Escaping the "Balkanizing" Gaze? Perceptions of Global and Internal Developmental Hierarchies in Romania. (August 2017) - Kiss, Tamás
The article presents the perceptions of global and internal developmental hierarchies in Romania. According to our empirical results, the Western-centred developmental paradigm has deeply penetrated the worldviews of ordinary people in Romania. As a consequence, national self-perceptions, respectively, constructions of internal regional and ethnic differences in Romania, are powerfully shaped by the idea of East–West developmental hierarchies. Melegh introduced the concept of an "East–West slope" to denote a discursive construction used since the eighteenth century. This construction suggests that there is a gradual decline of development (or "civilization") as one moves from the West (North West) toward the East (South East). The author argues that this framework not only defines how Romanians position themselves in the global developmental hierarchy but also how they define their internal (regional and ethnic) hierarchies. The article also discusses Todorova's concept of Balkanism. This interpretive framework not only defines the perceptions of external observers but (following a process of cultural penetration) may also shape the self-perceptions of those involved. This article argues that Romanians have succeeded in avoiding—at least partially—the most severe consequence of the "Balkanizing gaze, " which is a constant sense of inferiority. It is also important, however, that this Balkanizing gaze can be reproduced at a national/local level and (in interrelation with other types of developmental discourses) can organize internal hierarchies.